2022
DOI: 10.4236/ce.2022.139190
|View full text |Cite
|
Sign up to set email alerts
|

Framing the Effects of High-Impact Practices from a High-Impact Learning Perspective. A Review of Studies

Abstract: Due to developments in information and communication technology, increasing knowledge production in the economy, globalisation and changes in professional structures and expectations, the call for reshaping education to increase its impact in terms of value for societal demands has become acute. In addition, many scholars have formulated criticisms on the low impact of education and higher education specifically. For this reason, it is of great importance for higher education institutions and colleges to offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
(134 reference statements)
0
1
0
Order By: Relevance
“…Research has demonstrated several educational strategies known as High Impact Educational Practices (HIEPs) to have a significant impact on student progress. HIEPs can contain a variety of learning tactics, including problem-based learning, service learning, project-based learning, capstone courses, field experiences, and other active learning strategies, according to the national survey on student engagement (National Survey of Student Engagement, 2007, Arikan et al, 2022.…”
Section: Viii) High-impact Educational Practices (Hieps)mentioning
confidence: 99%
“…Research has demonstrated several educational strategies known as High Impact Educational Practices (HIEPs) to have a significant impact on student progress. HIEPs can contain a variety of learning tactics, including problem-based learning, service learning, project-based learning, capstone courses, field experiences, and other active learning strategies, according to the national survey on student engagement (National Survey of Student Engagement, 2007, Arikan et al, 2022.…”
Section: Viii) High-impact Educational Practices (Hieps)mentioning
confidence: 99%